Development of isolated panduratin A-loaded solid lipid nanoparticles as a transdermal delivery system for cosmeceutical products - Rangsimawong, Worranan; Jitsaeng, Kusuma; Duangjit, Sureewan; Sritananuwat, Phaijit; Opanasopit, Praneet (Science, Engineering and Health Studies, 2023)
Panduratin A (PA), isolated from Boesenbergia rotunda (L.) Mansf., is a cyclohexenyl chalcone derivative with low water solubility, from which a suitable transdermal delivery system could be developed to improve skin penetration. Solid lipid nanoparticles (SLNs) are carriers for lipophilic drugs to penetrate the skin layers. Therefore, the objective of this study was to develop SLN containing PA as a transdermal delivery system. Cytotoxicity studies in skin cells, (normal human fibroblasts (NHFs) and human immortalized keratinocytes (HaCaTs),) were evaluated. The PA-loaded SLN formulations were formulated and characterized. From the results revealed that PA was not toxic to NHF and HaCaT cells at 1 µg/mL concentrations, indicating no cytotoxicity of skin cells. SLN formulation 0.1%w/v of PA-loaded SLN (SLN4) exhibited favorable properties such as the nanometer size, negative zeta potential, and the highest entrapment efficiency at 99.81%. The release and skin permeation study showed that PA from SLN4 was released from and permeated through skin better than oil (control) at all sampling times. In conclusion, PA has no skin cell cytotoxicity and is suitable to be used as a cosmeceutical ingredient. SLN4 plays a ideal role as a transdermal delivery system of PA, resulting from its suitable physicochemical properties and ability to permeate the skin.